Validating a test to assess early childhood learners’ ability to perceive, express and appreciate emotions - Jose Miguel Mestre Navas; Rocío Guil Bozal; Fátima Martínez-Cabañas Rodríguez; Cristina Larrán Escandón; Gabriel González de la Torre Benítez (Revista Electrónica Interuniversitaria de Formación del Profesorado)
Emotional Education, regardless of the school level, has an important mission in the goal of any educational project: socialising younger generations. However, it is also important to assess implemented programs by means of a valid, reliable measure of the progression of children’s’ cognitive and emotional development. Using a sample of 138 early childhood learners (aged from 3 to 6) this paper tested an instrument for assessing the ability to perceive, appreciate and express emotions (as defined by Mayer & Salovey’s model, 1997; 2007). Also, external criteria were developed by teachers on several issues related to children’s social and personal adaptation (school rules, achievement, impulsiveness, social acceptance of peers and hostility). Findings suggest that children from 3 to 6 years who obtain best scores in the perception and assessment of basic emotions are considered by their teachers to better adjust to school rules, to better control impulses, to achieve better academic performance and to be less problematic. It is also important to note that the study is at its initial stages and presents some limitations, as certain important variables such as personality and verbal ability are not controlled. Nevertheless, it should be pointed out that children showed great enthusiasm in taking the test.